Ovarian Aging-Like Phenotype in the Hyperandrogenism-Induced Murine Model of Polycystic Ovary. (19th February 2014) - Rezvanfar, Mohammad Amin; Shojaei Saadi, Habib A.; Gooshe, Maziar; Abdolghaffari, Amir Hosein; Baeeri, Maryam; Abdollahi, Mohammad
Abstract : There are prominently similar symptoms, effectors, and commonalities in the majority of characteristics between ovarian aging and polycystic ovarian syndrome (PCOS). Despite the approved role of oxidative stress in the pathogenesis of PCOS and aging, to our knowledge, the link between the PCO(S) and aging has not been investigated yet. In this study we investigated the possible exhibition of ovarian aging phenotype in murine model of PCO induced by daily oral administration of letrozole (1 mg/kg body weight) for 21 consecutive days in the female Wistar rats. Hyperandrogenization showed irregular cycles and histopathological characteristics of PCO which was associated with a significant increase in lipid peroxidation (LPO) and reactive oxygen species (ROS) and decrease in total antioxidant capacity (TAC) in serum and ovary. Moreover, serum testosterone, insulin and tumor necrosis factor-alpha (TNF- α ) levels, and ovarian matrix metalloproteinase-2 (MMP-2) were increased in PCO rats compared with healthy controls, while estradiol and progesterone diminished. Almost all of these findings are interestingly found to be common with the characteristics identified with (ovarian) aging showing that hyperandrogenism-induced PCO in rat is associated with ovarian aging-like phenotypes. To our knowledge, this is the first report that provides evidence regarding the phenomenon of aging in PCO.